Talent Management as a Driver of Organizational Excellence: Evidence of Organizational Justice as a Mediator - Alkhawaldah, Reyad Abdallah; Alshawabkeh, Ziad Ali; Al Qaryouti, Mosa Qasim (International Review of Management and Marketing, 2026)
This study investigates the role of talent management (TM) in driving organizational excellence (OE) within Jordanian public universities, with organizational justice (OJ) posited as a mediating mechanism. Drawing on the Resource-Based View and Equity Theory, a quantitative approach was employed using data from 377 employees across Jordanian public universities. Structural equation modeling (PLS-SEM) revealed that TM significantly enhances both OJ and OE. Furthermore, OJ partially mediates the relationship between TM and OE, indicating that fair and transparent HR practices amplify the effectiveness of talent initiatives. The findings underscore the strategic importance of integrating fairness into TM systems to foster employee trust, engagement, and sustainable performance. This research contributes theoretically by validating OJ as a critical mediator and offers practical insights for university administrators aiming to align talent strategies with organizational excellence goals in public higher education settings.